Spiral of Silence: Polarizing Content Creation through Moderating Toxicity - Ying Bao; Jessie Liu (CESifo GmbH, 2025)
This paper investigates how content moderation affects content creation in an ideologically diverse online environments. We develop a model in which users act as both creators and consumers, differing in their ideological affiliation and propensity to produce toxic content. Affective polarization - users' aversion to ideologically opposed content - interacts with moderation in unintended ways. Even ideologically neutral moderation that targets only toxicity can suppress non-toxic content creation, particularly from ideological minorities. Our analysis reveals a content-level externality: when toxic content is removed, non-toxic posts gain exposure. While majority-group creators sometimes benefit from this exposure, they do not internalize the negative spillovers, i.e., increased out-group hostility toward minority creators. This discourages minority expression and polarizes the content supply, ultimately leaving minority users in a more ideologically imbalanced environment: a mechanism reminiscent of the "spiral of silence." Modeling creation as a strategic response to moderation, we underscore the importance of eliciting whether user engagement reflects toxicity or ideological disagreement in guiding platform governance.
Keywords: JEL-Codes; 330; content moderation; toxicity; polarization